2018
DOI: 10.1111/tid.12929
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus prophylaxis in seropositive renal transplant recipients receiving thymoglobulin induction therapy: Outcome and risk factors for late CMV disease

Abstract: These data indicate that antiviral prophylaxis adequately prevented CMV in seropositive recipients given ATG, but late disease still occurred. Low eGFR and low lymphocyte count at the end of prophylaxis may help identify patients at higher risk of CMV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 47 publications
2
25
1
Order By: Relevance
“…The incidence of HCMV‐disease in patients who use prophylactic or preemptive strategies declines when compared with non‐receiving renal transplant recipients . In this study, 7.3% of allograft recipients developed HCMV‐disease.…”
Section: Discussionmentioning
confidence: 61%
“…The incidence of HCMV‐disease in patients who use prophylactic or preemptive strategies declines when compared with non‐receiving renal transplant recipients . In this study, 7.3% of allograft recipients developed HCMV‐disease.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, we observed a low number of opportunistic infections in all types of SOT recipients frequently occurring at later timepoints following transplantation, once prophylaxis is discontinued. Better defining populations at risk for these opportunistic infections will be crucial to further improve the present prophylactic strategies, mostly designed for early infections [ 12 , 19–26 ]. Aspergillus fumigatus , responsible for 1.4% of all infections, is a serious concern, particularly in liver transplant recipients, because of the associated high mortality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This practice is supported by the previously identified risk from receiving this lymphocyte-depleting agent in CMV-seropositive KT recipients [3]. Reusing et al demonstrated some benefit of anti-CMV prophylaxis in CMV-seropositive KT recipients who received ATG in a retrospective study [14]. More recently, Chiasakul and colleagues implemented targeted prophylaxis in those receiving a standard dose of ATG among high-risk patients such as those who underwent ABO incompatible KT with a favorable outcome [4].…”
Section: Discussionmentioning
confidence: 89%